Technology-Based Islamic Religious Education Learning Innovation in the Independent Curriculum - Hasnahwati Hasnahwati; Tobroni Tobroni; Abdul Haris; Romelah Romelah (Didaktika: Jurnal Kependidikan, 2025)
It’s very important for education to answer the challenges of the times to prepare a generation that is able to face global change and the complexity of the future. The challenges of this era include social, economic, technological, and environmental changes that are developing rapidly. Innovation in the use of learning media is very necessary as an effort to maximize the learning process in the classroom. This is more directed at the cognitive dimension, namely mastery and understanding of Islamic Religious Education material, plus the progress of information and communication technology is currently increasingly rapid. This research is a library research with a descriptive-analytical approach. In collecting data, it is carried out through sources related to the research subject, such as books, journals, and the internet, analyzed and concluded. The results of this study are: First, Use of Applications: Interactive applications such as Kahoot, Quizizz, and Google Forms, as well as the Canva platform can be used to create interactive quizzes related to Islamic Religious Education material, Second, Learning Videos and animations: Content that tells the story of the prophet, Islamic history, or Islamic moral values can convey messages visually well and videos like this can be uploaded on platforms such as YouTube, and Third, Educational games with Islamic themes: Games with Islamic themes, such as quizzes about Islamic morals or adventures about the story of the prophet, can make students learn in a fun way. and play videos with ablution practices and prayer procedures, adjusted to the theme of Islamic Religious Education lessons.